Preparation and Characterization of Rubberwood Fiber- Polypropylene Composites - Morsal, Akramsadat Tayefeh (2007)
In this study, blending of rubberwood fiber with polypropylene and the effects of EBNR (ethylene-butene copolymer) as the compatibilizer, on the mechanical and thermal properties of rubber wood fiber, polypropylene composites were investigated by using FTIR, TGA, DMA and SEM. Composites were prepared at 10, 20, 30, 40, and 50 % by weight of fiber. Different fiber loadings, durations, temperatures, and rotation speeds process were tested to determine the optimum condition of blending. Consequently, the composite with 40% fiber loading, temperature at 175 °C, for 15 min and rotation speed of 40 rpm were selected to be the best composite. Mechanical tests including tensile, flexural and impact strength (notched and unnotched) were performed. In addition, water absorption study was carried out. The properties of composite without elastomer showed the reduction in tensile strength and impact strength (notched and unnotched) with increase in fiber loading, however the increase in tensile modulus, flexural strength and modulus of the composite was observed. The presence of EBNR in all loadings led to reduction in tensile and flexural strength and increased the impact strength. With attention to all aspects, the composite with 10% EBNR loading showed the best mechanical and physical properties. With the increased of fiber loading, the water absorption was also increased, and the addition of EBNR led to less water absorption, and the lowest absorption was observed for 10% EBNR loading. The result from FTIR analysis indicated that the interaction is only physical between components of the composite. The presence of EBNR on the composite made a weak improvement in thermal stability as shown by thermogravimetric analysis (TGA). DMA studies established that EBNR led to reduction of stiffness and enhancing mobility of the resulting composite. SEM micrographs gave clear indication of the effect of EBNR in reduction of void sizes and numbers, and close interaction of PP and fiber was clearly demonstrated for composite with elastomer.